PENGARUH LAYANAN BIMBINGAN KELOMPOKTERHADAP TINGKAT PENYESUAIAN DIRI SANTRI BARU SMA KELAS X DIASRAMA BABUSSALAM PEKANBARU - Alfi Ramadhani; Abu Asyari; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study, entitled "Effects of Group Guidance Service Level Adjustment To New Students High School Class-X in Babussalam Boarding Pekanbaru School Year 2013/2014". Researchaims: 1)To know the description of the level of adjustment of new students before giveng roup counseling services. 2)To know the description of the level of adjustment of new students after the giveng roup counseling services. 3)To determine differences in the level of adjustment of new students before and after group counseling services. 4)To determine the effect of group counseling services to the adjustment of new students. The population of this researchis a new class-X students of the school year 2013/2014. The sampling technique using the simple random sampling at random. The study design using the "one group pretest-posttest design" first of all measurements, subject to treatment for certain periodand then measured the second time. To determine the level of adjustment of students using aquestionnaire. Analysis of data using technique spercentage, to distinguish the adjustment of students before and after group counseling services use test "t" and obtained thitung greater than ttabel (-16.10>1.684) with a 5% error. Thus H0 rejected and Ha accepted, it means that there are significant differences on the adjustment of new students before and after group counseling services. Then the results of the test product moment coefficient of r=0.79 and determinant r2=0.63. Based on the results of research conducted, it can be concluded that onceheld group counselings ervices adjustment of new students of class-X SMA Babussalam rise of Pekanbaru.Keywords: Tutoring Services Group, Adjustment